Prognostic value of serum Uric Acid in-hospital Mortality and Morbidity in Patients with acute Myocardial Infarction (University Heart Journal, 2017)
Coronary artery disease (CAD) is one of the leading causes of death in the world and also in Bangladesh. This study was carried out to evaluate that Serum uric acid is a prognostic tool in acute myocardial infarction. In this study, 108 AMI cases were enrolled. All the patients were treated and managed identically by conventional standard management protocol. During hospital stay, patients were assessed for any kind of clinical outcomes e.g good recovery, mortality and morbidity (acute LVF, cardiogenic shock, arrhythmia and heart block). Patients with higher serum uric acid (SUA>6.5mg%, Group-II) were compared with Patients with lower serum uric acid (SUA